Deciphering the inflection points to achieve proficiency for each procedure step during training in laparoscopic appendicectomy. Issue 5 (14th September 2021) - Skjold-Ødegaard, B; Hamid, S; Lindeman, R -J; Ersdal, H L; Søreide, K
Abstract: Background: Laparoscopic appendicectomy is a common procedure early in surgical training. A minimum number is usually required for certification in general surgery. However, data on proficiency are scarce. This study aimed to investigate steps towards proficiency in laparoscopic appendicectomy. Methods: This was a prospective observational cohort study of laparoscopic appendicectomies performed by junior trainees under supervision scored on a six-point performance scale. Structured assessment was done within a defined programme. Procedures performed for uncomplicated appendicitis in adults were included. The procedures were evaluated with LOWESS graphs generated to investigate inflection points. Factors associated with proficiency rates were reported with odds ratios and 95 per cent confidence intervals. Results: In total 142 laparoscopic procedures were included for 19 trainees (58 per cent female). The cumulative number of procedures during the study was a median of 20 (i.q.r. 8–33). For overall proficiency, an inflection point occurred at 30 procedures. Proficiency rate increased from 51 per cent for 30 or fewer procedures to 93 per cent for more than 30 procedures (odds ratio 11.9 (95 per cent c.i. 3.4 to 40.9); P < 0.001). Inflection points for proficiency for each procedure step varied considerably, with lowest numbers (fewer than 15 procedures) for removing the specimen, and highest for dividing the mesoappendix (more than 55 procedures). Operating time was significantly reduced by a median of 7 minutes after 30 procedures, from median 62 (i.q.r. 25–120) minutes to median 55 (i.q.r. 30–110) minutes for more than 30 procedures. Conclusion: For junior trainees, variation in proficiency is related to specific procedure steps. Targeted training on specific procedure skills may reduce numbers needed to achieve proficiency in laparoscopic appendicectomy during training. Abstract : This article describes a study that aimed to investigate steps towards proficiency in laparoscopic appendicectomy. The conclusion was that for junior trainees, variation in proficiency is related to specific procedure steps. Targeted training on specific procedure skills may reduce numbers needed to achieve proficiency in laparoscopic appendicectomy during training.